One duck stuck - Root, Phyllis (Cambridge, Mass. : Candlewick Press, 1998)
In this counting book, increasingly larger groups of animals try to help a duck that is stuck in the sleepy, slimy marsh.
Keywords: Ducks; Marsh animals